Dermatosis neglecta: a case report - Devaraj, Yogesh; Mukunda, Ranga Swaroop; Shale, Mouryabha; Mittamedi, Nikitha Reddy; Yadav, Priyanka Yogananda; Sundaram, Premika Meenakshi (International Journal of Research in Dermatology, 2020)
Dermatosis neglecta or dermatitis neglecta is a condition which occurs due to inadequate cleansing of a localised area of skin resulting in the accumulation of dirt, sebum, sweat, corneocytes and bacteria. These patients do not clean the area due to various reasons like pain at the site, prior surgery, physical disability, neurological deficit, or psychiatric illness. Vigorous rubbing of the lesion with alcohol soaked gauze results in removal of the lesion. We report a case of dermatosis neglecta in a 50 year old lady with carcinoma breast following mastectomy on the right side. She did not clean the area adequately as she was scared that the area of suture after mastectomy would give way, thus resulting in hyperkeratotic lesions.